2021
DOI: 10.1186/s12936-021-03594-5
|View full text |Cite
|
Sign up to set email alerts
|

Rapid ethnographic assessment for potential anti-malarial mass drug administration in an outbreak area of Santo Domingo, Dominican Republic

Abstract: Background In the Dominican Republic, a recent outbreak of malaria in the capital, Santo Domingo, threatens efforts to eliminate the disease. Mass drug administration (MDA) has been proposed as one strategy to reduce transmission. The success of MDA is contingent upon high levels of acceptance among the target population. To inform the design of future MDA campaigns, this rapid ethnographic assessment examined malaria-related knowledge and attitudes toward malaria MDA among residents of a trans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
0
7
1
Order By: Relevance
“…Most people seem to learn about malaria through their friends, family, or television. In contrast to a rapid ethnographic study done in the same area in 2019, 15 CHWs were not as frequently cited as sources of information about malaria (mentioned by only 14.3%). This presents an unusual paradox: ethnographic work has found that many patients are misdiagnosed in clinical settings and later diagnosed in the community, leading them to look more favorably upon CHWs and others doing active surveillance.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Most people seem to learn about malaria through their friends, family, or television. In contrast to a rapid ethnographic study done in the same area in 2019, 15 CHWs were not as frequently cited as sources of information about malaria (mentioned by only 14.3%). This presents an unusual paradox: ethnographic work has found that many patients are misdiagnosed in clinical settings and later diagnosed in the community, leading them to look more favorably upon CHWs and others doing active surveillance.…”
Section: Discussioncontrasting
confidence: 59%
“…Most expressed motivation to participate in antimalaria MDA (55.1% were “very motivated” and 28.6% were “motivated”), a potentially useful strategy in this area. 15 , 16…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dialogic activities were performed less often. As indicated in the simplified table of results ( Table 1 ), health education strategies were the most common approach (n = 8, 44.4%) [ 53 55 , 58 60 , 62 , 67 ], followed by message design and dissemination (n = 7, 33.3%) [ 53 , 58 61 , 64 , 69 ], distribution of communication materials (n = 5, 27.8%) [ 53 , 54 , 59 , 67 , 68 ], and insertion of messages into existing networks and social structures (n = 5, 27.8%) [ 63 65 , 69 , 70 ]. Significantly, only a couple of cases used these four common strategies under a dialogic angle [ 64 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…As indicated in the simplified table of results (Table 1), health education strategies were the most common approach (n = 8, 44.4%) [53][54][55][58][59][60]62,67], followed by message design and dissemination (n = 7, 33.3%) [53,[58][59][60][61]64,69], distribution of communication materials (n = 5, 27.8%) [53,54,59,67,68], and insertion of messages into existing networks and social structures (n = 5, 27.8%) [63][64][65]69,70]. Significantly, only a couple of cases used these four common strategies under a dialogic angle [64,70]. Because the communication activities employed were diverse, it is important to briefly delineate the specific activities performed in these studies to reflect the array of approaches taken.…”
Section: Communication Actions In Lymphatic Filariasis (Lf) Eliminationmentioning
confidence: 99%